Strengthening the global health dialogue: linking research networks in the Global South - Roger, François; de Romémont, Aurelle; Binot, Aurélie; Loire, Étienne; Girard, Philippe (Perspective, 2019)
Version française de l'article Versión en español del artículo Myriad challenges arise when implementing health measures in middle- and low-income countries. Social, economic and sectoral constraints impede the application of research results and recommendations from national or international organizations. In these countries, platforms in partnership for research and training (dP) developed by CIRAD and partners in the health sector contribute unique and valuable experience. These platforms represent regional networks and foster intersectoral collaborative exchanges involving research, various social sectors and public and private governance levels. In the long term, they seek to develop networks of actors and policymakers while fostering innovation in different local and national contexts. This experience is now ripe for consolidating interactions at a more global level—linking regional health-oriented networks and building a platform of global scope. The concerned platforms collaborate to develop a shared vision of the targeted impacts and strategies to achieve them.